2014
DOI: 10.2147/cia.s69790
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status, dental treatment needs, and barriers to dental care of elderly care home residents in Lodz, Poland

Abstract: ObjectivesTo determine oral health status, dental treatment needs, and to identify barriers that prevent easy access to dental care by elderly care home residents in Lodz.BackgroundStudies in many countries show that oral health status of elderly care home residents is poor and there is an urgent need to improve it.MethodsThe study included 259 care home residents, aged 65 years and older. The oral examination was performed. In face-to-face interviews, subjects were asked about frequency of cleaning teeth and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 29 publications
(22 reference statements)
9
71
0
2
Order By: Relevance
“…Th ese results are consistent with the results of an investigation conducted among nursinghome residents in Holland, which found low salivary fl ow rates in 72% of the institutionalized elderly 26 . Salivary gland hypofunction may be correlated with various systemic disorders, medications, as well as the number of medications 3,11,27,28 . Th e higher incidence of decreased salivary fl ow rate which we found in the group of institutionalized elderly could be the result of a rather high number of diff erent medications or intake of medications with specifi c xerostomic side effects 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th ese results are consistent with the results of an investigation conducted among nursinghome residents in Holland, which found low salivary fl ow rates in 72% of the institutionalized elderly 26 . Salivary gland hypofunction may be correlated with various systemic disorders, medications, as well as the number of medications 3,11,27,28 . Th e higher incidence of decreased salivary fl ow rate which we found in the group of institutionalized elderly could be the result of a rather high number of diff erent medications or intake of medications with specifi c xerostomic side effects 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Some are unable to live independently as a result of their age and/or disease, and require institutionalization in long-term care facilities 1,2 . Multiple systemic diseases and their treatments can impair oral health and, consequently, the quality of life of an elderly person [3][4][5] . Th e most common oral diseases among the elderly are dental caries, tooth loss, gingivitis, periodontitis, decreased salivary fl ow, candidiasis, and oral cancer 2,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals need to understand how these changes lead to TMD, and how they affect pre-existing conditions (5) . It is important to bear in mind that the elderly may have complications of disease processes accumulated over their lifetime, which could lead to an increased prevalence of TMD in this age group (6,7) . Studies have shown that changes in systemic conditions may vary among the institutionalized and non-institutionalized elderly population (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…The principal of palliative care must be applied on both patients to maintain their general health and prevent the systemic condition getting worsen. 13 The invasive procedures for patients can be taken if the patient's condition improved. In Case 1 must enclose the recommendation from internist and laboratory results of the level of PT, APTT, complete blood count, and blood sugar.…”
Section: Discussionmentioning
confidence: 99%